1998
DOI: 10.1103/physrevb.57.789
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical stability of the polarization in a thin semiconducting ferroelectric

Abstract: The size effect in ferroelectrics is examined by considering the semiconductivity of the ferroelectric. This approach is applied to a theoretical investigation of the stability of the spontaneous polarization in a ferroelectric film on a semiconductor using a homogeneous Ginzburg-Landau theory. The band structure in the ferroelectric/insulator/semiconductor is rigorously incorporated in the theory, as if for a conventional semiconductor heterostructure such as GaAs/͑Ga,Al͒As. The carriers generated in the ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(138 citation statements)
references
References 50 publications
(33 reference statements)
10
118
0
Order By: Relevance
“…234,[385][386][387] In parallel, the properties of spatially separated ferroelectric-semiconductor systems were explored as driven by FeFET and FeRAM applications. [388][389][390][391][392][393] Much of these results are summarized in an excellent recent review by Hong et al 393 However, recent studies have demonstrated that in ambient conditions the screening is ionic in nature, and hence polarization dynamics at open surfaces should be considered as coupled surface electrochemical-bulk polarization switching process, as discussed in Section IV. Surprisingly the theory for such coupling was developed by Stephenson and Highland only recently, 229 and remained largely unused.…”
Section: Phenomenamentioning
confidence: 99%
“…234,[385][386][387] In parallel, the properties of spatially separated ferroelectric-semiconductor systems were explored as driven by FeFET and FeRAM applications. [388][389][390][391][392][393] Much of these results are summarized in an excellent recent review by Hong et al 393 However, recent studies have demonstrated that in ambient conditions the screening is ionic in nature, and hence polarization dynamics at open surfaces should be considered as coupled surface electrochemical-bulk polarization switching process, as discussed in Section IV. Surprisingly the theory for such coupling was developed by Stephenson and Highland only recently, 229 and remained largely unused.…”
Section: Phenomenamentioning
confidence: 99%
“…30 For the thick films considered here, we can also neglect the depolarization field due the finite conductivity of the PZT thin films. 31 The free energy is supplemented by the relevant mechanical boundary conditions for the mono/polydomain structures. 23,30 For the monodomain ferroelectric states, the mechanical boundary conditions give the in-plane strain components as The absence of forces acting on the free surfaces implies .…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…It is expected, therefore, that at the metal-ferroelectric contact a depletion zone and the corresponding (depletion) charge distribution is formed, similar to situation with usual semiconductor-metal contacts. The corresponding electronic structure and related effects were extensively discussed for layered metal-semiconducting ferroelectric systems [2][3][4][5][6][7][8]. The depletion effects are especially important in switching devices [6].…”
Section: Introductionmentioning
confidence: 99%